2017
DOI: 10.1016/j.pscychresns.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Imaging decision about whether to benefit self by harming others: Adolescents with conduct and substance problems, with or without callous-unemotionality, or developing typically

Abstract: We sought to identify brain activation differences in conduct-problem youth with limited prosocial emotions (LPE) compared to conduct-problem youth without LPE and community adolescents, and to test associations between brain activation and severity of callous-unemotional traits. We utilized a novel task, which asks subjects to repeatedly decide whether to accept offers where they will benefit but a beneficent other will be harmed. Behavior on this task has been previously associated with levels of prosocial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Seven of these used the Dictator Game ( Moor et al, 2012 ; Güroğlu et al, 2014 ; Will et al, 2016 , 2018 ; Schreuders et al, 2018 , 2019 ; Duell et al, 2021 ), and five used close variations on the Dictator Game, including either the Allocation Game ( Do and Telzer, 2019 ; Do et al, 2019 ), the Family Assistance Task ( Telzer et al, 2011 , 2013 ), or the Charity of Self Yield Task ( Spaans et al, 2020 ; Brandner et al, 2021 ). The seven remaining studies used various games that also involved resource distribution: the Socially Mindful task ( Lemmers-Jansen et al, 2018 ), the Altruism Antisocial Game ( Sakai et al, 2017 ), the Trust Game ( van den Bos et al, 2009 , 2011 ), the Public Goods Game ( Van Hoorn et al, 2016 ), and Cyberball ( van der Meulen et al, 2016 ; Tousignant et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of these used the Dictator Game ( Moor et al, 2012 ; Güroğlu et al, 2014 ; Will et al, 2016 , 2018 ; Schreuders et al, 2018 , 2019 ; Duell et al, 2021 ), and five used close variations on the Dictator Game, including either the Allocation Game ( Do and Telzer, 2019 ; Do et al, 2019 ), the Family Assistance Task ( Telzer et al, 2011 , 2013 ), or the Charity of Self Yield Task ( Spaans et al, 2020 ; Brandner et al, 2021 ). The seven remaining studies used various games that also involved resource distribution: the Socially Mindful task ( Lemmers-Jansen et al, 2018 ), the Altruism Antisocial Game ( Sakai et al, 2017 ), the Trust Game ( van den Bos et al, 2009 , 2011 ), the Public Goods Game ( Van Hoorn et al, 2016 ), and Cyberball ( van der Meulen et al, 2016 ; Tousignant et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the methodological differences described above, the reviewed studies focused on three different aspects of the decision-making process (see Table 1 , column “Aspect of Prosociality”). Eight studies compared (pro)social decision-making in general (i.e., the deliberation phase) to neutral/non-prosocial control conditions (hereafter, “prosocial decision-making”) ( van den Bos et al, 2011 ; Moor et al, 2012 ; Van Hoorn et al, 2016 ; Sakai et al, 2017 ; Lemmers-Jansen et al, 2018 ; Tousignant et al, 2018 ; Will et al, 2018 ; Duell et al, 2021 ). Eleven studies contrasted prosocial decision-making trials based on the actual prosocial choice such that decision-making with prosocial outcomes were compared to decision-making with non-prosocial outcomes (hereafter, “prosocial choices”) ( Telzer et al, 2011 , 2013 ; Güroğlu et al, 2014 ; Lemmers-Jansen et al, 2018 ; Schreuders et al, 2018 , 2019 ; Do and Telzer, 2019 ; Do et al, 2019 ; Spaans et al, 2020 ; van der Meulen et al, 2016 ; Brandner et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-one studies met the whole-brain inclusion criteria for the current meta-analysis. Of these studies, ten studies included two samples (Ewbank et al, 2018;Gregory et al, 2015;Hwang et al, 2016;Prehn et al, 2013b;Sakai et al, 2017;Sebastian et al, 2014;Sethi et al, 2018;van Lith et al, 2018;Viding et al, 2012b;White et al, 2015), resulting in a total of 71 samples. This represented a total of 1227 HC and 1328 CP/ASPD individuals (mean age = 20.15, range = 10.9-44.6 years old; 90 % males).…”
Section: Characteristics Of Included Studies For the Whole-brain Casementioning
confidence: 99%
“…1 PRISMA Flow Diagram * Papers were predominantly excluded for review purposes because CU measures were not used to assess the DSM-5 specifier symptoms. Other reasons were, for example, the use of CU measures that only enable to assess three of the four LPE specifier criteria (Colins 2016;Colins and Vermeiren 2013;Jambroes et al 2016), the lack of formal comparison of CD + LPE with CD Only youth (McMahon et al 2010), or lack of information about the assessment procedure followed to determine a CD diagnosis (Pechorro et al 2015); ** Two papers were identified after checking the references Sakai et al 2017), whilst three papers were identified by advance online publication explorations (Byrd et al 2018;Sethi et al 2018;Oldenhof et al 2018); *** Three of the five aforementioned potentially relevant papers were not included for review purposes because no measures of CD were used (Byrd et al 2018), and because youth who did not met criteria for CD also enrolled in the study whilst analyses were not run separately for youth with a CD diagnosis (Oldenhof et al 2018;Sakai et al 2017); **** Two papers used largely overlapping samples (Colins et al 2017;Van Damme et al 2016), but focused on a different research question, and therefore added significant incremental information to the review. Consequently, both papers were included for review purposes but will be treated as one and the same study magnitude of the significant group differences.…”
Section: Data-extraction and Data-analysismentioning
confidence: 99%